Vehicle Controls - Hrovat, Davor; Tseng, Hongtei E.; Lu, Jianbo; Deur, Josko; Assadian, Francis; Borrelli, Francesco; Falcone, Paolo (Control System Applications, Second Edition, 2011)
Vehicle control systems typically include chassis components that influence vehicle dynamics in three directions: longitudinal, lateral, and vertical. These three degrees of freedoms are controlled by chassis actuators such as brakes, steering, and suspensions, respectively. Traditionally, they were all mechanically controlled. For example, steering was actuated by the driver turning a steering wheel, which then caused the hydraulics in a power steering unit to amplify the driver-imposed torque and to create a desired wheel/tire rotation at the point of contact with the road.